E-038 Correlation analysis of endovascular treatment for ruptured intracranial aneurysm: predictors for unfavorable outcomes and recurrence. (22nd July 2019) - Yoon, W; Yoon, W; Roh, H; Suh, S; Kwon, T
Abstract : Purpose: The aim of this study is to identify significant predictors of unfavorable outcome and recurrence in the patients treated with endovascular treatment in the setting of ruptured aneurysms. Method and material: A total of 102 ruptured aneurysms of 102 patients who were treated with endovascular treatment including stent-assisted coil embolization and coil embolization without stent were enrolled in this study. In order to identify significant predictors of unfavorable outcome and recurrence, retrospective correlation analysis was performed. Result: A total of 72 patients (70.59%) showed favorable outcome (mRS 0–2) at their last follow up day and a total of 30 patients (29.41%) showed unfavorable outcome (mRS 3–6). On univariate and multivariate analysis for predictors of outcome in all grades SAH patients, initial Hunt-Hess grade (p=.018), periprocedural complications (p=.014), external ventriculostomy (EVD) presence (p=.030) were significant predictors of unfavorable outcome, whereas age (p=.009), re-bleeding before treatment (p=.002), EVD presence (p=.003), delayed cerebral ischemia (DCI) (p=.035) were significantly associated with unfavorable outcome in the patients with good grade SAH who were defined as initial Hunt-Hess grade 1–3. On univariate and multivariate analysis for predictors of recurrence, aneurysm volume (p=.043), initial Raymond classification (p=.038) had a significant correlation with recurrence. Conclusion: The rate of unfavorable outcome in this study of SAH patients treated with endovascular method was 29.41% and the recurrence rate was 20.59%. The present study demonstrates various predictors for unfavorable outcome and recurrence in the SAH patients treated with endovascular method. Therefore, careful individualized consideration in treatment for acute SAH patients who are planned to be treated with endovascular treatment is necessary. Disclosures: W. Yoon: None. W. Yoon: None. H. Roh: None. S. Suh: None. T. Kwon: None.